Cerclage wire or positional cortical screw for the treatment of intraoperative calcar fractures during primary total hip arthroplasty? A biomechanical study. (January 2023) - Gauthier, Paul; Slullitel, Pablo A.; Speirs, Andrew; Laude, Frederic; Gofton, Wade T.; Beaule, Paul E.
Abstract: Background: During primary total hip arthroplasty, intra-operative calcar fractures have been historically treated with cerclage wires. However, interfragmentary screw fixation technique can possibly achieve the same results with technical advantages. The aim of this biomechanical study was to assess stability of calcar fractures fixed using interfragmentary screw technique compared to a traditional cerclage system specifically in context of total hip arthroplasty. Methods: Thirty-two periprosthetic fractures were reduced using either a single cerclage cable or an intracortical positional screw perpendicular to the fracture line. Axial and torsional load testing was terminated after experimental model failure. Findings: No significant difference was obtained for all output parameters when comparing cerclage wires versus interfragmentary screw fixation respectively. Load at failure: 8043 ± 712 N vs 7425 ± 854 N ( p  = 0.115). Load at calcar fracture propagation: 6240 ± 2207 N versus 6220 ± 966 N ( p  = 0.668). Maximum stiffness before failure: 617 ± 115 N/mm vs 839 ± 175 N/mm ( p  = 0.100) and stiffness at calcar fracture propagation reached 771 ± 153 Nmm vs 886 ± 129 N/mm ( p  = 0.197). Torque to failure levels obtained were 59.4 ± 7.1 N*m vs 60.9 ± 12.0 N*m ( p  = 0.908). Torque to calcar fracture propagation, 51.6 ± 6.1 N*m vs 48.5 ± 9.8 N*m ( p  = 0.298). Torsional stiffness at failure, 0.38 ± 0.03 N*m\deg. vs 0.43 ± 0.13 N*m\deg. ( p  = 0.465). Torsional stiffness at calcar fracture propagation were 0.37 ± 0.03 N*m\deg. vs 0.45 ± 0.17 N*m\deg. ( p  = 0.462). Interpretation: The strength of fixation and stability of the implant were similar for both techniques. In the synthetic bone model tested, using an interfragmentary screw conveyed similar stability to the constructs in the management of an intra-operative medial calcar fractures. Thus, potentially giving surgeons an alternative option for intraoperative fracture fixation during primary total hip arthroplasty. Highlights: Intraoperative calcar fractures compromise implant stability. Classic calcar fracture fixation method not optimal for direct anterior approach. No difference in stability gained from screw versus cable in synthetic bone models.